Memahami Memahami Komunitas Basis Gerejawi (KBG) di Paroki St. Antonius Kali, Keuskupan Manado - Lando, Yohanis; Pangemanan , Stefhanus Hanny (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2024)
This article wants to look at the understanding of the Basic Ecclesiastical Community (KBG) in the parish of St. Antonius Kali. The author's interest in discussing this theme is because the KBG style of life has existed since the First Congregation (Acts 2 & 4). This style has been revived since the 1950s in Brazil, FABC 1990, SAGKI 2000 and specifically the Manado Diocesan Synod 2018. The problem studied is how the understanding and practice of KBG in the parish of St. Antonius Kali, Manado Diocese. In the explanation, the KBG theory is discussed, then the author uses qualitative-phenomenological research methods with observation and interview techniques. The field findings were analyzed using KBG theory. The author found that the KBG in Kali is known as the spiritual area. In practice, the spiritual area has the characteristics of KBG: local church base, local community base, lay empowerment base, apostolic base, transformative pastoral care base. The KBG aims to revive evangelical values so that they are manifested in life. One of the methods offered is FGD (Focus Group Discussion) to involve community participation.